The effect of minimum wage, open unemployment rate and economic growth on the gini ratio in indonesia in 2020-2024 in the perspective of islamic economics: Gini Ratio, Minimum Wage, Open Unemployment Rate, Economic Growth - Dea Aprilia; Dinda Fali Rifan; Taufiqur Rahman (Universitas Muhammadiyah Bengkulu, 2026)
This study analyzes the effect of the Minimum Wage, Open Unemployment Rate, and Economic Growth on the Gini Ratio in 10 Indonesian provinces with high inequality—DI Yogyakarta, DKI Jakarta, West Java, Gorontalo, Papua, West Papua, East Java, South Sulawesi, West Nusa Tenggara, and Central Java—during 2020–2024. Using a quantitative approach with panel data multiple linear regression, the analysis applies the Chow, Hausman, and LM tests, along with classical assumption tests. Data were obtained from the Central Statistics Agency. The results indicate that the Random Effect Model (REM) is the most appropriate model. The Minimum Wage, Open Unemployment Rate, and Economic Growth each show positive but insignificant effects on the Gini Ratio and are also jointly insignificant, suggesting that income inequality in these provinces is influenced more by factors beyond these variables